Living wages, equal wages : gender and labour market policies in the United States - Figart, Deborah M.; Power, Marilyn; Mutari, Ellen, 1956- (London : Routledge, 2002)
Focus on social reform movements for living wages and equal wages, this informative and accessible book explores how US wage regulations in the twentieth century took gender, race-ethnicity and class into account.
Includes bibliographical references and index.
lje 31/01/14
Loans
Keywords: Wages -- United States; Wages -- Government policy -- United States; Equal pay for equal work -- United States